2017
DOI: 10.1126/sciadv.1602803
|View full text |Cite
|
Sign up to set email alerts
|

Selective control of reconfigurable chiral plasmonic metamolecules

Abstract: DNA origami nanotechnology enables selective reconfiguration of plasmonic quasi-enantiomers through simple pH tuning.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
249
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(259 citation statements)
references
References 46 publications
(74 reference statements)
5
249
0
2
Order By: Relevance
“…DNA origami‐based dynamic systems expand the dynamic range to ≈100 nm with higher design complexity. The driving force of the dynamic nanomachines usually arises from DNA hybridization, strand displacement, or external stimuli such as electricity, pH, light, magnetic field, etc. For example, Castro and co‐workers reported the construction of complicated and reversible DNA robots by implementing the design principles of macroscopic mechanical machines .…”
Section: The Development Of Dna Nanotechnologymentioning
confidence: 99%
See 1 more Smart Citation
“…DNA origami‐based dynamic systems expand the dynamic range to ≈100 nm with higher design complexity. The driving force of the dynamic nanomachines usually arises from DNA hybridization, strand displacement, or external stimuli such as electricity, pH, light, magnetic field, etc. For example, Castro and co‐workers reported the construction of complicated and reversible DNA robots by implementing the design principles of macroscopic mechanical machines .…”
Section: The Development Of Dna Nanotechnologymentioning
confidence: 99%
“…In this work, the reconfigurable systems were driven by DNA hybridization and strand displacement. Later, they demonstrated that the environmental stimuli such as pH, light, and biomolecules could also be used as inputs to trigger the conformation state changes on the same plasmonic system. In addition, Jiang et al established a multistimuli response nanosystem based on reconfigurable DNA origami organized with AuNRs.…”
Section: Fabrication Of Dynamic Patterns On Dna Origamimentioning
confidence: 99%
“…DNAn anotechnology presents av ersatile platform for the directed self-assembly of discrete,c omplex plasmonic nanostructures. [10] Assemblies of DNA-coated gold nanoparticles on DNAo rigami scaffolds have been applied as waveguides, [11] as chiral sensors, [12] for surface-enhanced fluorescence, [13] and for SERS. [6,14,15] Notably,t here are only af ew studies with silver nanoparticles, [16,17] although silver offers strong field enhancements over ab road wavelength range,w hile gold aggregates are restricted to excitation at longer wavelengths.…”
mentioning
confidence: 99%
“…Diese werden selektiv so gebunden, dass sie sich bei den SERS-Messungen in dem Spalt mit der hçchsten Feldverstärkung befinden. B. bereits als Wellenleiter, [11] als chirale Sensoren, [12] füroberflächenverstärkte Fluoreszenz- [13] und fürS ERS-Messungen [6,14,15] verwendet worden. [10] Strukturen aus DNA-beschichteten Goldnanopartikeln auf DNA-Origami-Gerüsten sind z.…”
unclassified
“…[10] Strukturen aus DNA-beschichteten Goldnanopartikeln auf DNA-Origami-Gerüsten sind z. B. bereits als Wellenleiter, [11] als chirale Sensoren, [12] füroberflächenverstärkte Fluoreszenz- [13] und fürS ERS-Messungen [6,14,15] verwendet worden. Es gibt hingegen nur wenige Studien, in denen Silbernanopartikel zur Anwendung kommen, [16,17] obwohl Silber hohe Feldverstärkungen über einen breiten Wellenlängenbereich zu liefern in der Lage ist.…”
unclassified